Estimation of effects of tributyltin (TBT) bioaccumulation using the imposex character in marine gastropods (Thais tuberosa and Monodonta labio) - Noor, Sri Yuningsih; Rumengan, Inneke F. M; Lasut, Markus T (AQUATIC SCIENCE & MANAGEMENT, 2013)
The effects of tributyltin (TBT) have been estimated using imposex characters in two species of marine gastropods, Thais tuberosa and Monodonta labio, at 3 different locations along the Minahasa Peninsula, northern part of Sulawesi Island: Manado Bay Waters, Bitung Coastal Waters, and Tateli Coastal Waters as a control area. The estimation was done by comparing the percentage of female imposex (I) at different body size (small: shell length ≤ 25 mm; large: shell length >25 mm), and measuring the concentration of TBT in sediments and soft part of the gastropod samples. The highest I value was found in small sized T. tuberosa from Manado Bay Waters (63%) and large sized T. tuberosa from Bitung Coastal Waters (60%). Small and large sized M. labio had their highest I value, 30% and 44% respectively, in the samples from Manado Bay Water and Bitung Coastal Waters. The occurence of imposex in both speciesis correlated with the high concentration of TBT in sediments and soft part of the marine gastropod samples© Kajian tentang pendugaan pengaruh bioakumulasi logam berat tributyltin (TBT) menggunakan karakter imposeks pada gastropoda laut (Thais tuberosa dan Monodonta labio) telah dilakukan. Sampel diambil dari 3 lokasi di perairan sepanjang Semenanjung Minahasa, Pulau Sulawesi bagian Utara, yaitu Perairan Teluk Manado (PTM), Perairan Bitung (PBT), dan Perairan Pantai Tateli (PPT) sebagai lokasi kontrol. Pendugaan dilakukan dengan cara membandingkan persentase individu imposeks (I) sampel ukuran kecil (K; panjang cangkang ≤ 25 mm) dan ukuran besar (B; panjang cangkang >25 mm), dan pengukuran konsentrasi TBT pada sedimen dan bagian lunak sampel gastropoda laut. Nilai I tertinggi adalah pada T. tuberosa ukuran K asal PTM, sebesar 63%, dan ukuran B asal PBT, sebesar 60%.Untuk M. labio baik ukuran K maupun B, nilai I tertinggi adalah pada sampel asal PTM dan PBT, masing-masing sebesar 30% dan 44%. Kejadian imposeks pada kedua jenis sampel ini didukung dengan konsentrasi TBT pada sedimen dan jaringan gastropoda laut yang tinggi©